Modulatory effects of trophoblast-secreted CXCL12 on the migration and invasion of human first-trimester decidual epithelial cells are mediated by CXCR4 rather than CXCR7 - Jiayi Zheng; Haiping Wang; Wenhui Zhou (BMC, 2018)
Abstract Background Maternal-fetal crosstalk during embryo implantation is complex and regulated by local signaling molecules. Chemokines and their receptors are critical signaling components required for implantation and the process of pregnancy. This study aimed to explore whether human first-trimester trophoblast cells (TCs) were capable of modulating the migration and invasion of human first-trimester decidual epithelial cells (DECs) via CXCL12/CXCR4/CXCR7 signaling. Method The expression of CXCR4 and CXCR7 in DECs was examined by immunohistochemistry, immunocytochemistry, immunofluorescence, flow cytometry, real-time polymerase chain reactions and western blotting. The effects of recombinant human CXCL12 (rhCXCL12) and TC-conditioned medium (TC-CM) on DEC viability in vitro were explored using a viability assay. The modulatory effects of rhCXCL12 and TC/DEC co-cultures on DEC migration and invasion were examined with migration/invasion assays. Result CXCR4 and CXCR7 were co-expressed in human first-trimester DECs. Human rhCXCL12 and TC-CM had no effects on DEC viability in vitro (P > 0.05). Both exogenous CXCL12 and co-culture with TCs significantly increased the migration and invasion of DECs (P < 0.05). Neutralizing antibodies against CXCR4 (P < 0.05) or CXCL12 (P < 0.05), but not CXCR7 (P > 0.05), significantly blocked the enhanced migration and invasion of DECs induced by exogenous CXCL12 or TC co-culture. Conclusions CXCR4 and CXCR7 were co-expressed in human first-trimester DECs. TC-derived CXCL12 promoted the migration and invasion of DECs via CXCR4, but not CXCR7, in a paracrine manner during early pregnancy.